Minimally Invasive Distal Metatarsal Osteotomies for Metatarsalgia Treatment: A Review - Mario Suárez-Ortiz; Sofía Mora-Pardo; Miguel López-Vigil; Francisco Muñoz-Piqueras; Alfonso Martínez-Nova (Surgical Techniques Development)
Introduction: Metatarsalgia is a very common pathology in podiatric consultations, whose main aetiological factor is biomechanical alterations. Given the failure of conservative treatments, minimally invasive osteotomies of the distal metatarsal are becoming more popular, providing comparable results to open surgical techniques and with a lower rate of complications. Objectives: To determine clinical improvement and patient satisfaction after minimally invasive distal metatarsal osteotomy (DMMO) as a surgical treatment for central metatarsalgia at present. Methodology: The databases used for this systematic review were PubMed, Scielo, Cochrane Library, WOS and Scopus. We included articles that studied the efficacy of DMMO for primary metatarsalgia and excluded studies whose patients had more than one pathology or used other surgical techniques. Results: We identified 10 articles, 5 prospective studies, 4 retrospective studies and 1 cross-sectional, non-randomized, analytical study published between 2015 and 2021. The total number of subjects was 366, with a mean age of 61 years. The majority of subjects were women. They presented with symptomatology compatible with primary metatarsalgia for a minimum of 6 months and had failed conservative treatment. Conclusions: DMMO osteotomies for central metatarsals offer excellent post-surgical results for the treatment of central metatarsalgia in the assessment scales (AOFAS, MOXFQ etc.) of the articles analyzed and therefore an evident clinical improvement with benefits in terms of MTF mobility and reduction of surgical time, as well as a high degree of satisfaction in the patients who received this intervention that can be considered as excellent.